Report of judgments, advisory opinions and other decisions of the African Court on Human and Peoples’ Rights African Court Law Report Volume 1 (2006-2016) (Pretoria University Law Press (PULP), 2021)
This Volume covers all judgments, including separate and dissenting opinions, advisory opinions, rulings, decisions, procedural orders and orders for provisional measures delivered by the Court between 2006 and 2016. Each of the cases in the Report includes a brief summary of the case together with key words and corresponding paragraph numbers that indicate the exact paragraph in the judgment where the Court discussed the highlighted issues. A subject matter index highlights the various subjects that the cases dealt with. ‘’Considering that the Court has not had any law report since its establishment, the publication of this Volume is a significant milestone. It will be an immeasurable aid to researchers and practitioners alike,’’ according to the President of the Court, Hon Justice Sylvain Oré. He added that in publishing the Report, the Court has significantly eased the challenges of access to its case law.